A simple computational model for scleral stiffness assessments via air-puff deformation OCT - De La Hoz, Andres; Villegas, Lupe; Marcos, Susana; Birkenfeld, Judith S. (Frontiers in Bioengineering and Biotechnology, 2024)
The mechanical properties of the sclera are related to its structural function, and changes to these properties are believed to contribute to pathologies such as myopia. Air-puff deformation imaging is a tool that uses an imaging system coupled with an air-puff excitation source to induce and measure deformation in a tissue in vivo. Typically used for the study of the cornea’s mechanical properties and IOP, this tool has been proposed as a method to evaluate scleral stiffness. In this work, we present a computational model of the rabbit eye to assess scleral deformation under air-puff. Parametric studies were conducted to evaluate the effects of material properties, intraocular pressure, and other parameters on the deformation response. Output from the model was also compared to experimental measurements of air-puff deformation in rabbit eyes under varying IOP. Central deformation response was found to be most influenced by material properties of the sclera (at site of air-puff and posterior), thickness, and IOP, whereas deformation profile was most influenced by material properties. Experimental and simulated IOP dependence were found to be similar (RMSE = 0.13mm). Scleral APDI could be a useful tool for quick in vivo assessment of scleral stiffness.